MORAL EDUCATION IN THE FORMATION OF CHARACTER FOR EARLY CHILDHOOD IN THE ERA OF MORAL CRISIS - Nurjanah, Ayudia Sri; Zuhrita Rahma, Ita; Gunawan, An Nafi’ah Indana Lazulfa; Rasiin, Rasiin (Program Studi Pendidikan Agama Islam, 2025)
This article discusses the need of moral education in fostering positive human traits in the face of societal etiquette crises. Using literary analysis, the study shows that concepts like empathy, honesty, and responsibility can be effectively expressed through role models, habits, advice, and inspirational stories. In addition to the effects on families and schools, improper use of technology can also have negative effects. This article also discusses negative effects of digital media, hedonistic tendencies, and a lack of positive role model. Education based on the Qur'an and the Sunnah is considered essential for raising morally upright generations, with cooperation between families, schools, and the general public as a key component of its success.